KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH: FAKTOR YANG MEMPENGARUHI DAN IMPLIKASI KEBIJAKAN (Studi Pada SKPD Pemerintah Provinsi Jawa Tengah) - Febrian Cahyo Pradono; Basukianto . (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2015)
This research was based onthe insufficiency of local government financial statements in Central Java. This research aims to determine the factors that influencing on low quality of local government financial statements and the problems / constraints that faced by SKPD on preparation of financial statements. Financial statement has an important role on formulating development policies. The low quality of financial statement may provide inaccurate informations for policy makers. Inaccurate informations may result inaccuracy of policy formulation, which made a negative impact on the development of an institution. Based on lower quality of local government financial statement, this needs to be given special attention. This research was an explanatory research of 48 SKPDs in Central Java Provincial Government, using of questionnaires in data collection. There were 141 data collected which details : Expenditure Treasurers (46 questionnaires), Goods Administrators (47 questionnaires), and Financial Statement Staffs (48 questionnaires). The results showed that the competence of human resources, information technology, reconciliation and internal control systems have significant effect on quality of local government financial statement, while the role of PKK - SPKPD has no significant effect.Keywords: Financial statement quality, competence of human resources, information technology, reconciliation, the role of PPK-SKPD, and internal control systems.